(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This study aims to compare the CSR Livelihood Programs of Public and Private Sector Companies. This study is designed to compare the CSR Livelihood Program of Public and Private Sector Companies. This study aims to look into the effectiveness of Corporate Social Responsibility (CSR) livelihood programs of government and non-governmental organizations and how it influences the beneficiaries' socio-economic development. The research method is quantitative with the framework of SEM that aims to analyze the relationship between variables that are important in determining the outcomes of livelihoods. The study results show that the major constructs, which are latent, are CSR Program Design, Skill Development Initiatives, Resource Accessibility, Community Participation, Livelihood Improvement, and Beneficiary Satisfaction, where CSR Program Design, Skill Development Initiatives, Resource Accessibility, and Community Participation are independent variables and Livelihood Improvement and Beneficiary Satisfaction are dependent variables. Furthermore, the concept of the Sustainability of Livelihood is taken into account as a mediating variable to understand the long-term impacts. Structured questionnaires are used to gather primary data from beneficiaries of the selected CSR programs in both public and private sector companies. For statistical validity, a sample size of about 300-400 respondents is considered as valid. The hypothesized relationships and the structural paths between the two sectors are tested using the SEM model. The results will show striking differences in the implementation and impact of CSR livelihood approaches. It is hypothesized that the private sector companies will be more efficient and innovative in their delivery of the program, and the public sector companies will have wider outreach and inclusivity. The study also seeks to establish the factors that have been critical in contributing to sustainable livelihood development. The research builds on existing literature by conducting a comparative study on SEM, which allows for insights for policy makers, business strategists, and development practitioners to improve the efficiency and sustainability of CSR.